CYP2C19 Gene Profiling as a Tool for Personalized Stress Ulcer Prophylaxis With Proton Pump Inhibitors in Critically Ill Patients - Recommendations Proposal - Bořilová Linhartová, Petra; Zendulka, Ondřej; Janošek, Jaroslav; Mlčůchová, Natálie; Cvanová, Michaela; Daněk, Zdeněk; Kroupa, Radek; Bartošová, Ladislava; Lipový, Břetislav (Frontiers in Medicine, 2022)
To this date, there are no recommendations for personalized stress ulcer prophylaxis (SUP) in critical care that would take the patient´s individual genetic predispositions into account. Of drugs used for this purpose, proton pump inhibitors (PPIs) are the first-choice drugs in intensive care unit patients. The degradation of proton pump inhibitors is mediated by cytochrome P450 (CYP) enzymes; in particular, CYP2C19 and, to a lesser extent, CYP3A4 are involved. Expression and metabolic activity of, in particular, CYP2C19 is significantly affected by single nucleotide polymorphisms, the drug metabolization rate varies greatly from ultrarapid to poor and likely influences the optimal dosage. As these CYP2C19 predictive phenotypes via CYP2C19 haplogenotypes (rs12248560/rs4244285) can be relatively easily determined using the current standard equipment of hospital laboratories, we prepared a set of recommendations for personalized PPI-based stress ulcer prophylaxis taking into account the patient’s CYP2C19 predictive phenotype determined in this way. These recommendations are valid, in particular, for European, American and African populations, because these populations have the high representations of the CYP2C19*17 allele associated with the overexpression of the CYP2C19 gene and ultrarapid degradation of PPIs. We propose the CYP2C19 gene profiling as a tool for personalized SUP with PPI in critically ill patients.